Associations between birth-related expectation violations and postpartum somatic symptoms and stress in mothers - Pia Eitenmüller; Ana Maria Fiesel; Siegmund Köhler; Pia von Blanckenburg; Hanna Christiansen (Journal of Affective Disorders Reports)
Background: The impact of unmet expectations on birth satisfaction and thus postpartum mental health has been described. Despite the high prevalence of postpartum mental distress, the direct influence of birth-related expectation violations has hardly been investigated. In this study, we explored the impact of birth-related expectation violations on postpartum maternal somatic symptoms and stress. Methods: Our sample consisted of 125 women who filled out two surveys on childbirth expectations, on somatic symptom severity and psychosocial stress (German Patient Health Questionnaire; PHQ-D); during pregnancy (T1) and after birth (T2; up to six months postpartum). We identified expectation violations concerning pain, mode of birth, interaction with clinical staff and midwives, birth complications and support from partner/companion through evaluative qualitative content analysis and calculated their predictive power for postpartum somatic symptoms and stress via two regression analyses. Results: Regression analyses yielded significant results, explaining 40.7 % of higher postpartum somatic symptoms with more negative expectation violation in mode of birth and the primiparous status. Overall, 38.7 % of higher postpartum stress was explained by more negative expectation violations with birth mode as the only predictor. Limitation: A deductive approach to assess birth-related expectations might have contributed to biased responses, the retrospective assessment of birth experiences to biased recall. Further control variables such as pregnancy complications or the actual mode of birth should be investigated. Conclusion: Our study revealed that unmet expectations about the birth mode significantly affect postpartum mental health. This suggests a potential opportunity for preventive measures to foster realistic childbirth expectations and thus enhance the overall birth experience.